Management of Recurrent Entropion in Traumatic Proptosis: Poster Presentation - Case Report - Ophthalmologist - ANGGA KARTIWA; George Raden Mas Said; Niluh Putu Ayu Dewi Wardhani; Shanti Fitrianti Boesoirie; Mohamad Rinaldi Dahlan (Majalah Oftalmologi Indonesia, 2023)
Introduction : Shortening of posterior lamella due to fibrotic tissue is the pathomechanism of cicactricial entropion. It may be complicated by proptosis in a post traumatic patient which may require repeated repair procedure. Case Illustration : A 29-year-old woman came with complaints of protruding left eye since being hit by an iron tip 2 months prior. She also complained off double vision. Left eye presenting visual acuity was 0.08 with hipotropic position, proptosis, lid retraction, and entropion of the inferior lid. CT scan examination showed unremarkable results. The patient then underwent forced duction test, exploration, and muscle restriction release on the left eye, followed by inferior rectus recess and superior rectus resect procedures 3 months later. A month later the patient underwent entropion repair in the left eye using the tarsal fracture method. However, a week later the patient complained of a recurrent entropion, thus a grey line splitting procedure combined with retractor repositioning and tightening of the tarsus was performed. At the 7 days follow-up time, the eyelid margin was succesfully everted with an acceptable result. Discussion : Skin graft procedure is one of the option for cicatricial entropion. However, its risk of recurrences and more difficult secondary repair can be harrowing. Thus, a grey line splitting procedure is an alternative that can be considered. Conclusion : Combined procedure of grey line splitting, retractor repositioning, and posterior lamellar tightening showed a good cosmetic result in an uncommon case of entropion.